Biologically active indolizidine alkaloids. Issue 2 (31st October 2020) - Zhang, Junmin; Morris‐Natschke, Susan L.; Ma, Di; Shang, Xiao‐Fei; Yang, Chen‐Jie; Liu, Ying‐Qian; Lee, Kuo‐Hsiung
Abstract: Indolizidine alkaloids are chemical constituents isolated from various marine and terrestrial plants and animals, including but not limited to trees, fungi, ants, and frogs, with a myriad of important biological activities. In this review, we discuss the biological activity and pharmacological effects of indolizidine alkaloids and offer new avenues toward the discovery of new and better drugs based on these naturally occurring compounds. Graphical Abstract: The bioactivities of indolizidine alkaloids.